Preferensi Konsumen Jamu Terhadap Jamu Gendong (Studi Kasus: Kelurahan Sumompo, Kecamatan Tuminting, Kota Manado, Provinsi Sulawesi Utara) - Yustika Apriyanti Umasangadji; Nordy F. L. Waney; Celcius Talumingan (AGRI-SOSIOEKONOMI, 2022)
This research aims to determine the characteristics of herbal consumers and analyze consumer preferences for “Jamu Gendong”. This research was carried out for 1 month, starting from November to December 2020. The data used in this study were primary data and secondary data. Primary data were obtained from direct interviews with herbal drink consumers and herbal sellers. Secondary data were obtained from the Monograph of Sumompo Village and literature related to the research. The sampling method used in the selection of respondents was done by accidental sampling technique with the number of respondents 50 people. The results of this study indicate the characteristics of “Jamu Gendong” consuments in Sumompo Village in terms of gender, most of them are female, seen from the work of most of them are manual workers, seen from the purpose of consuming herbal drink is to maintain health (promotive). The consumer preference for herbal drink in Sumompo Village shows the overall attributes of the herbal drink with a total score of 7.11, which means that it is very good in the eyes of consumers.